Indonesian Influence on English Errors in X Tweet - Annajmi Mastari Maryam; Wulandari Wulandari; Veriyansah Veriyansah; Atika Hanum; Siti Ismahani (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
This study aims to analyze grammatical errors found in English tweets posted by Indonesian users on X. The research focuses on identifying the types of errors based on Error Analysis theory and explaining their causes through Contrastive Analysis between Indonesian and English. This study employs a qualitative descriptive method, with data collected from a number of tweets containing grammatical errors. The errors are classified into four categories: omission, addition, misinformation, and misordering. Furthermore, the sources of errors are analyzed into interlingual and intralingual factors. The findings reveal that misinformation is the most dominant type of error, followed by omission and addition, while misordering occurs less frequently. These errors include incorrect verb forms, misuse of articles, inappropriate word choices, and incorrect sentence structures. Most errors are categorized as intralingual, indicating that they are mainly caused by incomplete understanding of English grammar rather than direct influence from Indonesian. However, some errors reflect interlingual influence, particularly in the omission of articles. In addition, the study shows that the informal nature of social media contributes to the use of non-standard language forms. In conclusion, both linguistic competence and contextual factors influence learners’ grammatical accuracy in online communication.